BANKRUPTCY PREDICTION MODEL, GROWTH, LEVERAGE AND ACCEPTANCE OF GOING CONCERN OPINION - Nanik Niandari; Eka Noor Asmara; Djaja Perdana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The research aims to test the influence of bankruptcy prediction models, company growth, and leverage ratios on the possibility of a company receiving a going concern audit opinion. The dependent variable of this research is receipt of going concern audit opinion while the independent variables of this research are bankruptcy prediction models, company growth and leverage ratios. Manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period were selected as samples determined using a purposive sampling technique. The sample was 179 companies with a total of 761 observations. The data was analyzed using a logistic regression model. The test results show that the leverage ratio is proven to have a positive influence on the acceptance of going concern audit opinions. On the other hand, the bankruptcy prediction model and company growth have no influence on the acceptance of going concern audit opinions.